1999
DOI: 10.1159/000007637
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Intravenous Octreotide Treatment for Acute Experimental Pancreatitis

Abstract: Background: The efficacy of octreotide, the synthetic analogue of the hormone somatostatin, for the treatment of acute pancreatitis is controversial. Octreotide has been commonly administered in subcutaneous bolus injections; however, continuous intravenous infusion may be advantageous for acute conditions. Methods: Acute experimental pancreatitis was induced in rats by intraparenchymal injections of 1 ml 10% sodium taurocholate, and octreotide (1 µg/kg/h, dissolved in physiological solution, intravenously was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Upon the theory that inhibition of pancreatic secretion may be beneficial in acute pancreatitis, researches began in early 1980s with conflicting reports. 10,11,[14][15][16][21][22][23] Choi et al 10 saw a "beneficial local effect" and remarked that "local inflammation was supressed by somatostatin treatment." Even when better clinical outcomes were seen, the results failed to prove a statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the theory that inhibition of pancreatic secretion may be beneficial in acute pancreatitis, researches began in early 1980s with conflicting reports. 10,11,[14][15][16][21][22][23] Choi et al 10 saw a "beneficial local effect" and remarked that "local inflammation was supressed by somatostatin treatment." Even when better clinical outcomes were seen, the results failed to prove a statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…23 Paran et al, Kaplan et al, and Greenberg et al reported that OA has positive effects in some pancreatitis models in rats, biochemically and histopathologically. [24][25][26] Despite these studies, Sanchez Manuel et al reported that OA does not have a positive effect, either histopathologically or biochemically, in pancreatitis. 27 It has been reported that free oxygen radicals play an important role in the pathogenesis of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of octreotide on pancreatitis has been investigated in several experimental and clinical trials 2–12 . However, the results are inconsistent as different models of pancreatitis were used and the optimal treatment modality, dosage and route of administration have not been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Although decreasing effects of octreotide on pancreatic autodigestion were observed in several trials [2][3][4][5][6][7][8][9][10][11][12][13] results remain inconclusive concerning doses and time of application in AP. In terms of the mechanism of octreotide it has been demonstrated that somatostatin and related analogs (octreotide) decrease lipid peroxidation in septic rats 14 by inhibition of activated neutrophils and monocytes, 15,16 which normally increase oxygen radicals and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%